Left atrial strain as evaluated by two-dimensional speckle tracking predicts left atrial appendage dysfunction in patients with acute ischemic stroke - Sasaki, Shintaro (BBA Clin, 2014)
BACKGROUND: Left atrial appendage (LAA) dysfunction predisposes patients with atrial fibrillation (AF) to cardioembolic stroke. Two-dimensional (2D) speckle tracking was reported to be useful for evaluating left atrial (LA) regional function, as well as left ventricular function. However, it remains unclear whether 2D speckle tracking is useful for evaluating LAA dysfunction. Therefore, we investigated whether decreased LA strain may predict LAA dysfunction and thrombus formation in patients with acute ischemic stroke. METHODS: We performed transthoracic and transesophageal echocardiography in 120 patients (83 males, mean age 72 ± 11 years) within 7 days of onset of an acute ischemic stroke. Longitudinal LA strain was evaluated using 2D speckle tracking imaging at each LA segment, and peak systolic strain was calculated by averaging the results for each segment. RESULTS: Forty-eight patients had LAA dysfunction as defined by the presence of LAA thrombus and/or severe spontaneous echo contrast. LA peak systolic strain was significantly decreased in patients with LAA dysfunction compared to those without (32.3 ± 13.7% vs. 12.1 ± 7.2%, p < 0.0001). LA peak systolic strain was significantly correlated with LAA emptying flow velocity (r = 0.693, p < 0.0001). The optimum LA peak systolic strain cut-off value for predicting LAA dysfunction was 19%. Multivariate logistic regression analysis showed that LA peak systolic strain was an independent predictor of LAA dysfunction (odds ratio 0.059, 95% confidence interval 0.018–0.146; p < 0.0001). CONCLUSION: Decreased LA peak systolic strain was independently associated with LAA dysfunction in patients with acute ischemic stroke.